Gramofon v službi sakralne glasbe? - Kunej, Drago (Muzikološki zbornik, 2014)
Like most activities in the gramophone industry, recording sacred music appears to have been linked with trade and profit. Through the example of gramophone records released by the Ljubljana Cathedral Choir and the Adria Singers from the USA, one can see that favourable market results depended upon a number of factors. By comparing the popularity of recordings of these two choirs, with the number of surviving records, one can conclude that the sale of sacred music lagged behind that of secular.
Keywords: gramofonske plošče; komercializacija glasbe; popularizacija sakralne glasbe; sakralna glasba